Clinical heterogeneity and differential diagnosis of atopic dermatitis. (9th May 2014) - Deleuran, M.; Vestergaard, C.
Summary: Atopic dermatitis (AD) is a chronic or chronically relapsing skin disease that usually presents for the first time before the age of 20 years. The disease displays great clinical heterogeneity and may resemble a number of different disorders, making the correct diagnosis of AD a significant challenge for physicians. Based on the Hanifin and Rajka criteria, the authors outline the common symptoms of AD and provide an overview of the differential diagnoses to help distinguish AD from other conditions within the clinic.